(untitled) (Journal of the College of Basic Education, 2023)
It is noted that educational and educational institutions at the level of public education in Iraq still depend on memorization and memorization in teaching all social subjects and the lack of use of effective teaching methods, which led to a decline in academic achievement and then a decline in the scientific level of students in social subjects in general and geography In particular, the problem of low achievement of students in geography is one of the problems facing teachers and researchers in the field of teaching and learning. It is reflected in the later stages that knowledge is cumulative.The subject of geography is one of the important subjects in the life of the learner, as it deals with the study of man and the environment and the interaction between them. It is one of the materials that contain different concepts and terms that are difficult for students to understand, if it is presented in an abstract way. If we look at the educational reality in Iraq, we find that it does not allow students to practice activities on their own. On the traditional theoretical aspect represented by deaf memorization without interest in the participation of students, their communication and their interaction with the material, which raised the researcher’s feeling of the research problem as follows:1 . The use of geography teachers for teaching methods based on indoctrination, memorization and memorization, and the lack of use of modern educational methods and models, and this is indicated by each of the studies (Al-Rubaie, 2008) and (Al-Jumaili, 2005).2 . The social subjects are considered a major subject among the various school curricula subjects that deal with in their studies the human being and the surrounding environment and the interaction that takes place between them and the problems that arose as a result of that. Values, attitudes and beliefs. And since social education is so important, there is no doubt that it needs teaching methods that make its lessons palatable and distinctive, that inspires students with curiosity, trains them to think, and puts in their hands distinguished and selected experiences. (Abu Sarhan, 13, 2000)3 . And since the social materials aim to prepare the student for life as an influential, effective and productive citizen who is aware of his role in the way of the progress and advancement of the student in order to achieve a bright future for this country. It is necessary to achieve these goals that the curriculum of social subjects in the preparatory stage and (Al-Khayyat, 15, 1996) is the stage of the basis of education, a developed and renewed curriculum based on a sound basis that includes our Arab and Islamic principles and values and accommodates everything that is new and contemporary that goes along with these principles .4 . The Ministry of Education in Iraq directed all teaching staff to the need to follow up on modern trends and aspects of innovation in teaching methods in order to try them out and benefit from them (Ibrahim, 1989, 9).5 . Geography is a subject of study with a distinct nature and very important goals that are difficult to bring into practice and application without the use of methods, methods and teaching aids commensurate with the nature of its various topics (Al-Laqani 1979.7).6 . Effective teaching requires understanding what students know and need to learn, and then providing the challenge and support needed for quality learning. It also requires knowledge and understanding, as well as understanding students as learners. Increase knowledge and understanding of teaching strategies. Teachers should identify the prior learning of their students. A good teacher knows how to ask questions, and how to plan the lesson in order to reveal the knowledge of his previous students, then he can design experiences and lessons that suit previous learning and build on it. Thus, students learn and understand geography and build new knowledge based on previous knowledge. ((NCTM, 2000).The experiences teachers provide play a major role in determining the extent and quality of students’ learning. Students’ understanding of geographical ideas can be ensured throughout their studies if they actively engage in tasks and experiments designed to deepen and relate their knowledge. Students’ learning with comprehension can be supported by:Classroom learning, when students present ideas, learn to evaluate their own and others’ ideas, and develop their thinking skills. Dialogue and interaction between students can be used in the classroom, which leads them to identify the links between ideas, and to reorganize their knowledge. throughWhen students talk about their own strategies, teachers can confirm their latent knowledge and build on it, in addition to that in such situations, procedural skills and conceptual comprehension can be developed through problem solving, logical thinking, and argument evaluation (NCTM, 2000).The research conducted by Piaget in the cognitive growth and development of the individual is the basis for the constructivist philosophy. Piaget developed an integrated theory about cognitive development in children, and this theory has two partsThe first is called logical determinism, while the second part is called constructivism, which is related to the issue of building knowledge, constructivism, in which Piaget clarified the principle of building knowledge, and by it he means that the individual builds his knowledge of himself and does not receive it negatively from others (Daoud, 2003).